2018
DOI: 10.1016/j.jhep.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

A novel orally available small molecule that inhibits hepatitis B virus expression

Abstract: We discovered a novel small molecule viral expression inhibitor that is highly selective for HBV and unlike current therapy inhibits the expression of viral proteins by specifically reducing HBV mRNAs. RG7834 can therefore potentially provide anti-HBV benefits and increase HBV cure rates, by direct reduction of viral agents needed to complete the viral life cycle, as well as a reduction of viral agents involved in evasion of the host immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(130 citation statements)
references
References 37 publications
(43 reference statements)
8
116
0
1
Order By: Relevance
“…Differentiated HepaRG hepatoma (dHepaRG) and dHepaRG asialoglycoprotein receptor 1/2 (ASGPR1/2) cell lines were infected by HBV genotype D as described . Primary human hepatocytes (PHHs) isolated by the collagenase perfusion method from chimeric urokinase‐type plasminogen activator/severe combined immunodeficiency (uPA/SCID) mice with humanized livers were obtained from PhoenixBio (Hiroshima, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Differentiated HepaRG hepatoma (dHepaRG) and dHepaRG asialoglycoprotein receptor 1/2 (ASGPR1/2) cell lines were infected by HBV genotype D as described . Primary human hepatocytes (PHHs) isolated by the collagenase perfusion method from chimeric urokinase‐type plasminogen activator/severe combined immunodeficiency (uPA/SCID) mice with humanized livers were obtained from PhoenixBio (Hiroshima, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…However, these trials were recently terminated because of formulation toxicities . Interestingly, a recent study has identified a novel small molecule inhibitor that can reduce viral messenger RNA (mRNA) and pgRNA expression . Despite strong evidence that RG7834 does not function in as RNAi, it is not yet clear how this therapeutic agent can suppress HBV transcription in a virus‐specific manner.…”
Section: Novel Therapeutic Strategies In Developmentmentioning
confidence: 99%
“…They are likely to interact with host functions that mediate these processes, and given how unusual are their structures (found more often in noncoding than in coding RNAs), they may present opportunities for antiviral targeting. Curiously, there is evidence that HBV pregenomic RNA may use the host TRAMP pathway normally used for quality control and degradation of defective host transcripts, for its maturation (Javanbakht et al, 2017; Mueller et al, 2018; Zhou et al, 2018). …”
Section: Transcription Of Cccdna and Transport Of Rna Out Of The Nucleusmentioning
confidence: 99%
“…Recently, we and others have reported that a small molecule, a dihydroxyquinoline, can cause the rapid degradation of HBV transcripts (Mueller et al, 2018; Zhou et al, 2018). The degradation occurs in the nucleus, and is selective, to the extent that most other host transcripts and proteins tested are not significantly affected, over the period of study.…”
Section: Transcription Of Cccdna and Transport Of Rna Out Of The Nucleusmentioning
confidence: 99%